Qualitative and quantitative molecular analysis of bacteria in root canals of primary teeth with pulp necrosis - Samira Salomão LEMOS; Dionéia Evangelista CESAR; Stefânia Werneck PROCÓPIO; Fernanda Campos MACHADO; Luiz Claudio RIBEIRO; Rosangela Almeida RIBEIRO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Information about bacterial diversity, such as the number of each species in the root canals of primary teeth, contributes to improving our effective management of infections of endodontic origin in primary teeth. This study made a qualitative and quantitative assessment of the bacteria in the root canals of primary teeth with necrotic pulp, using the fluorescence in situ hybridization (FISH) technique. Thirty-one primary teeth with pulp necrosis from 31 children were evaluated using the FISH technique, to detect the presence and density of Aggregatibacter actinomycetemcomitans, Campylobacter rectus, Enterococcus faecalis, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens, Streptococcus, Streptococcus mutans, Streptococcus sobrinus, Tannerella forsythia and Treponema denticola. Descriptive measures explained the data related to density, and Student's t-test assessed the differences among the densities of each bacterium, according to signs and symptoms. The bacterial density was paired and correlated. All bacteria tested were detected and identified in all the samples. The average number of bacterial individuals from each species ranged from 1.9 x 108 cells/mL (S. mutans) to 3.1 x 108 cells/mL (F. nucleatum) (p > 0.05). The sum of the mean counts of each bacterium represented almost 80% of the entire microbial community. Patients with pain had significantly more T. denticola, and those with edema showed a greater density of Streptococcus and P. nigrescens (p < 0.05). This study revealed that all 12 bacteria evaluated were found in all primary teeth with pulp necrosis. There was no predominance among the species studied; all species had a similar number of individuals.